Magnesia doped Ag/Al2O3 - sulfur tolerant catalyst for low temperature HC-SCR of NOx - More, Pavan M.; Jagtap, Neelam; Kulal, Atul B.; Dongare, Mohan K.; Shubhangi B. Umbarkar (Applied Catalysis B-Environmental, 2014)
A series of magnesia doped Ag/Al2O3 catalysts were prepared by modified impregnation method using boehmite as alumina precursor. The prepared catalysts were characterized and tested for the SCR of NOx using propene as reductant under lean condition. Doping of magnesia improved the low temperature catalytic activity for HC-SCR of NOx as well as sulfur tolerance. Maximum 98% NO conversion with 100% selectivity for N-2 was obtained at 350 degrees C with 7% Mg doping to Ag/Al2O3. The improvement in low temperature activity and the sulfur tolerance has been correlated to decreased acidity after addition of magnesia to alumina support. In situ FTIR study showed that the deactivation in the presence of SO2 was due to the sulfation of silver and aluminum sites in Ag/Al2O3 catalyst, however its formation was suppressed in case of magnesia doped Ag/Al2O3 improving its sulfur tolerance. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: HC-SCR; Low temperature activity; NOx; Sulfur tolerance

Molybdenum(VI) dioxo complexes for the epoxidation of allylic alcohols and olefins - Pandhare, Swati L.; Jadhao, Rajesh R.; Puranik, Vedavati G.; Joshi, Pranaya V.; Capet, Frederic; Dongare, Mohan K.; Shubhangi B. Umbarkar; Michon, Christophe; Agbossou-Niedercorn, Francine (Journal of Organometallic Chemistry, 2014)
Several molybdenum(VI) dioxo complexes have been investigated as catalyst precursors for allylic alcohol epoxidation using mainly hydrogen peroxide as oxidant. All catalysts proved to be efficient and selective for the epoxidation of allylic alcohols provided the olefins were rather electron rich. Indeed, electron poor substrates could be converted selectively into the corresponding unsaturated aldehydes. A chiral dioxomolybdenum complex based on an optically pure tridentate Schiff base ligand was synthesized and characterized. Though that complex provided an efficient epoxidation catalyst for allylic alcohols and olefins, no chiral induction was observed. During the X-ray diffraction analysis, the cooling at 100 K led to the appearance of super-lattice reflections on diffraction patterns reflecting an ordering of the structure. Instead of one organometallic species observed at 298 K, three similar complexes of the same molecular structure could be observed in the asymmetric unit at 100 K. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Allylic alcohol; epoxidation; Molybdenum; Oxidation; Peroxide